A Solution to the 'Must Of' Problem Richard Coates. - Coates, Richard (Distributed by ERIC Clearinghouse, 1989)
It is possible to construct a case for the child's interpretation of "of" in "must of been" as the preposition "of" in the process of language acquisition. Assuming the familiar concept that linguists should construct the simplest analysis compatible with a phenomenon, it is suggested that some children construct a simplest analysis of such utterances as inevitably containing "of," using a grammar allowing such a structure. Evidence supporting such a structure comes from such constructions as the infinitive, where the word "to," a word with certain unambiguously prepositional functions, occurs ("to do"). If the learner eventually acquires standard English and demonstrates this by writing "must have been," he has replaced this earlier grammatical guesswork with a structure more normally and traditionally considered appropriate for the mature standard dialect. (MSE)